2008
DOI: 10.1074/jbc.m708369200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Vinyl Reductase Gene Essential for the Biosynthesis of Monovinyl Chlorophyll in Synechocystis sp. PCC6803

Abstract: The vast majority of oxygenic photosynthetic organisms use monovinyl chlorophyll for their photosynthetic reactions. For the biosynthesis of this type of chlorophyll, the reduction of the 8-vinyl group that is located on the B-ring of the macrocycle is essential. Previously, we identified the gene encoding 8-vinyl reductase responsible for this reaction in higher plants and termed it DVR. Among the sequenced genomes of cyanobacteria, only several Synechococcus species contain DVR homologues. Therefore, it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 34 publications
6
112
0
Order By: Relevance
“…It was found that the absorption peak of the Soret band shifted to a longer wavelength by about 10 nm. The absorption spectrum of the same mutant reported by Ito et al (2008) showed a shift by 6 nm in the Soret band. Judged from the absorption spectrum, the peak of the mutant seems to be affected by the higher amount of carotenoids.…”
Section: Spectral Characteristicsmentioning
confidence: 64%
See 4 more Smart Citations
“…It was found that the absorption peak of the Soret band shifted to a longer wavelength by about 10 nm. The absorption spectrum of the same mutant reported by Ito et al (2008) showed a shift by 6 nm in the Soret band. Judged from the absorption spectrum, the peak of the mutant seems to be affected by the higher amount of carotenoids.…”
Section: Spectral Characteristicsmentioning
confidence: 64%
“…Judged from the absorption spectrum, the peak of the mutant seems to be affected by the higher amount of carotenoids. This may account for the difference of peak positions between our data and those of Ito et al (2008). Figure 3B shows changes of absorption spectra of the mutant cells grown under the high-light condition (300 mE m 22 s 21 ).…”
Section: Spectral Characteristicsmentioning
confidence: 82%
See 3 more Smart Citations